Religious Education as A Pillar of Student Moral Development - Arienti Samiza; M. Aqillah Naufanda Febro; Adinka Rahmadani; M. Dylan An Agustia Fatta; Eva Iryani (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study examines the role of religious education as a foundational pillar in shaping students’ moral character in higher education. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews, observations, and document analysis involving students, lecturers, and academic stakeholders. The findings reveal that religious education plays a strategic role not only as a source of moral values but also as a mechanism for internal control, moral filtering, and value integration in students’ academic lives. However, the study identifies a gap between students’ cognitive understanding of religious teachings and their actual moral practices, indicating that value internalization remains incomplete. The research further finds that core moral values such as integrity, responsibility, tolerance, and self-regulation can be effectively internalized through contextual, reflective, and experiential learning strategies. The integration of religious values becomes more meaningful when supported by consistent institutional culture, exemplary educators, and relevant pedagogical approaches. This study contributes a holistic framework for strengthening religious education as a transformative process, offering both theoretical and practical implications for developing morally grounded and socially responsible graduates in contemporary higher education contexts.